IMPLEMENTASI NILAI PEMIKIRAN WILLEM ISKANDAR DALAM PEMBELAJARAN SEJARAH - kartika siregar (Institut Pendidikan Tapanuli Selatan, 2018)
The presented research elucidates the values of Willem Iskandar’s books, Si Bulus Bulus Si Rumbuk Rumbuk, and those functions in commemorating the student’s memory about the character education, religiosity, and nationalism. Descriptive qualitative was employed as research approach. The data were collected through literature reviews and content analysis of Si Bulus Bulus Si Rumbuk Rumbuk. The analysis focuses on the description of values inside of the Willem Iskandar’s poetry and contextual aspect that underlying it. The result of research portrays that the Willem Iskandar’s poetry contains the norms that construct the behavioral pattern of Mandailing society. The proses have a function in shaping the character and evolving the movements against the Dutch colonialism. In the educational dimension, the values inside of Willem Iskandar’s poetry become important to be studied in line with the problem of global capitalism that stimulates identity turmoil in any aspect of human life.